Collateral Consequences of Conviction in South Carolina Courts: A Study of South Carolina Defense Lawyers. (25th July 2022) - Leasure, Peter; Burrow, John; Zhang, Gary; Boehme, Hunter M.
Abstract: Recognizing the negative impacts of collateral consequences, policy-makers and scholars have sought to implement formal and informal standards aimed at increasing defendant notice of such consequences before pleading guilty. However, very few studies have sought to explore the actual practices of court room actors regarding collateral consequence notice. The current study filled this gap in knowledge using a survey of South Carolina defense lawyers. Specifically, South Carolina defense attorneys were surveyed about their practices regarding collateral consequence notice as well as their observations of judicial practices regarding collateral consequences. Results indicate that while a large majority of defense attorneys felt that it was their responsibility to inform their clients of collateral consequences, only 36% of respondents agreed that attorneys do a good job informing clients about collateral consequences. In fact, few respondents noted that they always inform their clients about collateral consequences that ex-offenders, probation and parole officers, and social workers consistently identify as particularly impactful to a successful reentry (those related to employment, housing, civic rights, and public benefits) and many never or rarely do so. However, 94.3% of respondents noted that they commonly discuss other collateral consequences with clients. Further, respondents noted that few judges always or often discuss collateral consequences. These results suggest that some collateral consequences are being discussed with some defendants, but also that these practices are inconsistent. Informed by these findings, recommendations for increasing defendant notice of collateral consequences are discussed.